MOTORIC STATUS RELATIONS IN MONTENEGRIN YUOTH POPULATION OF VARIOUS SPORT ORIENTATIONS - Duško Bjelica; Jovica Petković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
Volleyball and handball have become the most interesting sports disciplines from the very moment they became familiar to the Montenegrin population. The authors point out the fact that almost the whole Montenegrin young population practice these sports and that it would be of the greatest importance to pay a special attention to the psychological development of one part of the sensitive and peculiar Montenegrin population. The objective of the paper is to form an opinion about the motoric status of the handball and valleyball players, the students of the Faculty of Sports and Physical Education and the non- sportsmen and to compare it to the situation in the neighbouring countries as well as the comprehension of the issue how various sports activities influence the motoric development of the examinees.